Sensorimotor tests in patients with neck pain and its associated disorders : a systematic review and meta-analysis - Särkilahti, Niklas; Hirvonen, Milka; Lavapuro, Joona; Takatalo, Jani; Löyttyniemi, Eliisa; Tenovuo, Olli (Springer Nature, 2025)
This systematic review aimed to synthesize the current evidence regarding neck sensorimotor testing in individuals with neck pain, assess the differences between neck pain groups and healthy controls, and recognize factors that might affect test results. We performed the data search using PubMed, Embase, PsycINFO, CINAHL, and Scopus databases. We used a two-step screening process to identify studies. Furthermore, we screened the reference lists for additional studies. Hedges g was used to present the difference between neck pain groups and asymptomatic individuals. We assessed the quality of the studies using the QUADAS tool. The final review included 34 studies, of which 25 were related to the joint position error test, four to the smooth pursuit neck torsion test and six to the balance test. Our meta-analysis showed poorer joint-position sense, oculomotor function, and wider postural sway in individuals with neck pain than healthy controls. The size of the difference between the groups seemed to be influenced by the intensity of the pain and the presence of dizziness. Therefore, it might be helpful in future studies to differentiate patients with neck pain into subgroups based on their symptom and demographic profiles to assess other factors that significantly affect cervical sensorimotor control.